Digital Green: Participatory Video for Agricultural Extension - Gandhi, Rikin; Veeraraghavan, Rajesh; Toyama, Kentaro; Ramprasad, Vanaj (Information Technologies for International Development, 2009)
Digital Green is a research project that seeks to disseminate targeted agricultural information to small and marginal farmers in India using digital video. The unique components of Digital Green are: (1) a participatory process for content production; (2) a locally generated digital video database; (3) a human-mediated instruction model for dissemination and training; and (4) regimented sequencing to initiate new communities. Unlike some systems that expect information or communication technology alone to deliver useful knowledge to marginal farmers, Digital Green works with existing, people- based extension systems and aims to amplify their effectiveness. While video provides a point of focus, it is people and social dynamics that ultimately make Digital Green work. Local social networks are tapped to connect farmers with experts, the thrill of appearing “on TV” motivates farmers, and homophily is exploited to minimize the distance between teacher and learner. In a 13-month trial involving 16 villages (eight control and eight experimental villages balanced for parameters such as size and mix of crops) and a total of 1,470 households, Digital Green increased the adoption of certain agriculture practices seven-fold over a classic Training and Visit-based (T&V) extension ap- proach. On a cost-per-adoption basis, Digital Green was shown to be 10 times more effective per dollar spent than a classical extension system. Investments included performance-based honoraria for local facilitators, a shared TV and DVD player in each village, and one digital camcorder and PC shared across the project area. The results are preliminary, but promising.